Analysis of the Effects of Aggressive Shot Peening on Fatigue Life of 7075 – T6 Aluminum Alloy - Jabur, Khairallah S. (Al-Khwarizmi Engineering Journal, 2012)
For many years controlled shot peening was considered as a surface treatment. It is now clear that the performance of control shot peening in terms of fatigue depends on the balance between its beneficial (compressive residual stress and work hardening) and beneficial effects (surface hardening).The overall aim of this paper is to study the effects of aggressive shot peening on fatigue life of 7075 – T6 aluminum alloy. The fatigue life reduction factor (LRF) due to the aggressive shot peening was established and empirical relations were proposed to describe the behavior of LRF, roughness and fatigue life. The benefits of shot peering in terms of fatigue life are dependent on the shot peening time (SPT). The higher SPT is the lower the benefit is. Higher roughness results in lower fatigue life.